Personal and Socio-Economic Characteristics of Dairy Farmers of Valsad District of Gujarat (Indian Journal of Animal Production and Management, 2024)
A field survey was conducted in Valsad district of Gujarat to ascertain the personal, socio-economic  characteristics of dairy farmers and data were collected randomly from 240 dairy animal owners  through personal interview with the help of structured interview schedule. The present study revealed  that majority of the owners were belonged middle age group, literate, nuclear type of family with more  number of children making big size family. Most of the respondents were from schedule tribe category  having medium level of extension contacts and mass media exposure with membership in one  organization. Only few of the respondents were landless categories. Majority of respondents had  small herd size and they possessed agriculture and livestock as their livelihood.
Keywords: Dairy animals; characteristics; personal; socio-economic